Sclerotherapy in the Treatment of Endometrioma: A Comprehensive Systematic Review - Suparno; Novia Dwi (The International Journal of Medical Science and Health Research, 2024)
Background: This systematic review aims to provide a comprehensive evaluation of the literature on sclerotherapy for the treatment of endometrioma over the past decade, highlighting significant findings and identifying trends. Methods: A meticulous review process was undertaken, involving the evaluation of abstracts and titles to assess their relevance to the study objectives. Only full-text, English-language articles published between 2014 and 2024 were considered. Strict inclusion criteria were applied, excluding editorials, submissions without a DOI, previously published reviews, and duplicate entries. Results: The review included a diverse range of studies that investigated various aspects of sclerotherapy for endometrioma. Despite some studies indicating better outcomes with surgery, sclerotherapy demonstrated comparable PR and a minimal incidence of complications. Conclusions: Sclerotherapy for endometrioma appears to be a viable alternative to surgery, particularly in cases where preserving ovarian function and minimizing complications are prioritized. The heterogeneity in methodologies, including the type and concentration of sclerosing agents used, suggests a need for standardized protocols.